The automated will: Nonconscious activation and pursuit of behavioral goals. - John A. Bargh; Peter M. Gollwitzer; Annette Y. Lee-Chai; Kimberly Barndollar; Roman Trötschel (2001)
It is proposed that goals can be activated outside of awareness and then operate nonconsciously to guide self-regulation effectively (J. A. Bargh, 1990).Five experiments are reported in which the goal either to perform well or to cooperate was activated, without the awareness of participants, through a priming manipulation.In Experiment 1 priming of the goal to perform well caused participants to perform comparatively better on an intellectual task.In Experiment 2 priming of the goal to cooperate caused participants to replenish a commonly held resource more readily.Experiment 3 used a dissociation paradigm to rule out perceptual-construal alternative explanations.Experiments 4 and 5 demonstrated that action guided by nonconsciously activated goals manifests two classic content-free features of the pursuit of consciously held goals.Nonconsciously activated goals effectively guide action, enabling adaptation to ongoing situational demands.We must give up the insane illusion that a conscious self, however virtuous and however intelligent, can do its work singlehanded and without assistance.-